2021
DOI: 10.7759/cureus.15296
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Disease Severity and Resting Electrocardiograms of Adults With Sickle Cell Anemia in a Tertiary Institution in Southern Nigeria

Abstract: Dic-Ijiewere et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…There was no significant association between the mean age of the study participants or their gender (p = 0.49 and 0.87, respectively). A similar study conducted by Dic-Ijiewere et al among 120 South Nigerian sickle cell cases in 2021 showed 23%, 65%, and 12% of total cases falling under mild, moderate, and severe disease, respectively, with a mean score of 14.5 ± 4.04 [ 13 ]. There was no significant association between severity grade and age groups or gender in the study.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…There was no significant association between the mean age of the study participants or their gender (p = 0.49 and 0.87, respectively). A similar study conducted by Dic-Ijiewere et al among 120 South Nigerian sickle cell cases in 2021 showed 23%, 65%, and 12% of total cases falling under mild, moderate, and severe disease, respectively, with a mean score of 14.5 ± 4.04 [ 13 ]. There was no significant association between severity grade and age groups or gender in the study.…”
Section: Discussionmentioning
confidence: 89%
“…Dic-Ijiewere et al reported that as the severity of SCA increased, mean P-wave duration, P-wave dispersion, QRS dispersion, QTc interval, and QTc dispersion also increased. For QTc interval and QTc dispersion, these changes were statistically significant (p = 0.003 and p = 0.002, respectively) [ 13 ]. These observations raise suspicion about the metabolic cause of these dispersions secondary to hypoxia or toxins (hyperbilirubinemias).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations